Physico-chemical and catalytic properties of Fe-MKSF catalyst: Influence of MKSF clay as catalyst support - Hidayati Abdullah, Nur; Aida Zubir, Nor; Khairul Azam Selamat, Mohammad; Alrozi, Rasyidah; Nasuha, Norhaslinda; Imam Maarof, Hawaiah; Ballinger, Benjamin; Motuzas, Julius; C. Diniz da Costa, João (International Journal of Engineering and Technology, 2018)
The heterogeneous Fenton-like reaction is one of the most promising and effective treatment methods for the degradation of organic pollutants. In the present study, a detailed investigation on synthesis, characterization, and catalytic activity studies for oxidative degradation of methyl orange (MO) solution by iron oxide-immobilized montmorillonite KSF (Fe-MKSF) and pristine iron oxide catalysts were performed. The catalysts were synthesized via an impregnation-hydrothermal method using an autoclave reactor. Interestingly, the Fe-MKSF showed the highest catalytic removal of MO (85%) compared to the pristine iron oxides (30%) and MKSF (52%). This finding is well supported by the significant increase in surface area of the Fe-MKSF compared to the pristine catalysts (105.8 m2/g [Fe-MKSF] vs 52.2 m2/g [iron oxide] and 74.2 m2/g [MKSF]). The increased in surface area is favorable in having high accessibility of reactants towards the catalystsâ€™ active sites which enable to diminish limitations in mass transfer during the reaction. These traits proved to be essential for the improved catalytic activity of the Fe-MKSF catalyst.Â Â Â